2003
DOI: 10.1097/01.ju.0000062300.71507.3a
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment of Primary Grades IV and V Vesicoureteral Reflux in Children With Subureteral Injection of Polytetrafluoroethylene

Abstract: STING is a simple, safe and effective outpatient procedure for grades IV and V vesicoureteral reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 17 publications
1
16
0
7
Order By: Relevance
“…15 En 2003 se presentó un trabajo 16 sobre los resultados a largo plazo y el seguimiento a los 17 años de 717 casos con uréteres con RVU de alto grado (IV y V); del total, sólo 9 pacientes (1,2%) presentaron recidiva de RVU, lo que confirma por qué este material es considerado, por numerosos autores, la primera opción en caso de RVU de alto grado. A pesar de los resultados a largo plazo del PTFE, los datos sobre la posible migración de sus partículas no pueden ignorarse y, por esta razón, se han buscado y experimentado otras sustancias inyectables.…”
Section: Reflejo Vesicoureteral Tratamiento Endoscópico / 351unclassified
“…15 En 2003 se presentó un trabajo 16 sobre los resultados a largo plazo y el seguimiento a los 17 años de 717 casos con uréteres con RVU de alto grado (IV y V); del total, sólo 9 pacientes (1,2%) presentaron recidiva de RVU, lo que confirma por qué este material es considerado, por numerosos autores, la primera opción en caso de RVU de alto grado. A pesar de los resultados a largo plazo del PTFE, los datos sobre la posible migración de sus partículas no pueden ignorarse y, por esta razón, se han buscado y experimentado otras sustancias inyectables.…”
Section: Reflejo Vesicoureteral Tratamiento Endoscópico / 351unclassified
“…Different kinds of injection materials including polytetrafluoroethylene (Teflon), silicone, cross-linked bovine collagen and dextranomers in sodium hyaluronan (DiHA) have been used for injection with various success rates [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The long-term tissue effects of these materials are still obscure due to lack of clinical and experimental data in spite of wide spectrum usage for vesicoureteral reflux and incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…The literature consists of many papers which support our approach for the treatment of grade V VUR [6,9,12] . On the other hand, Chertin et al [13] have reported successful results of the ESI procedure for grade V VUR. They emphasized that there was no difference between patients with grade V and grade IV VUR with regard to success rates.…”
Section: Discussionmentioning
confidence: 99%